Kurikulum Geografi di Sekolah-Sekolah Menengah - Khalid, Khatijah (Penerbit Universiti Sains Malaysia, 1983)
This paper focuses on the development of the Malaysian secondary school syllabus in the context of educational changes which have taken place in recent times. This iisue is seen in the light of the geography syllabus currently used in secondary schools in Malaysia, and the efforts takJn by the Ministry of Education, Malaysia, in the process of curriculum development within the wider framework of the proposed General Education for Malaysian schools.